Increasing English as a Foreign Language Students’ Interest in Speaking Through Project-Based Learning in West Jakarta - Napitupulu, Sherin Melani; Juhana, Juhana; Marasabessy, Fachria Y (Universitas Pahlawan Tuanku Tambusai, 2026)
This study investigates the impact of Project-Based Learning (PBL) on enhancing the interest and speaking proficiency of elementary EFL students. Employing a mixed-methods case study design, the research was conducted with grade four students at Kalam Kudus III Christian Elementary School, Jakarta. Data were gathered through speaking tests, interviews, and questionnaires to evaluate the effectiveness of PBL, identify implementation challenges, and assess student engagement. The findings reveal that: (1) students’ speaking skills significantly improved following the intervention; (2) primary challenges included limited vocabulary and initial difficulties in peer collaboration; and (3) the approach effectively boosted students’ motivation and interest in English communication. Consequently, PBL serves as a viable pedagogical strategy to foster active oral participation in young learners.